Using Time-Driven Activity-Based Costing (TDABC) to Rationalize Hotel Service Costs - Youssef Fadhil Shlash (Research Parks Publishers, 2024)
In our world, the number of hotels that provide entertainment and tourism services is increasing, and most hotels are in fierce competition with each other. In order to prepare accurate data on the cost of the guest during his stay, a new method of cost accounting has been developed to keep pace with fierce competition and rapid technological progress. This method is represented by the method of cost accounting based on time-driven activities (TDABC). Its main objective is to test the impact of applying the cost system based on time-specific activities in rationalizing the costs of hotel services. The theoretical aspect showed the concept of this system, its advantages, criticisms and the components directed at it. The study adopted the case study method at the Agnar Tourist Hotel. It is a five-star hotel and the ability of the hotel employees to provide all the information necessary to develop the cost system used in the hotel. In order to prepare the research for the practical aspect, the researcher relied on the accounting data in the hotel records, the research sample and personal interviews with the hotel employees. The study was conducted in 2018. The study concluded that the hotel management can rely on the data issued by the time-driven activity-based costing (TDABC) system. The use of this system in the hotel distinguishes between practical energy and achievable energy. Because the cost of the guest is calculated in the system by estimating the practical energy of each of the activities carried out in the hotel.